Post performance stretching for the tennis player: Active-isolated stretching - McCaw, A. (Medicine and Science in Tennis, 2009)
About tennis specific stretching and especially the active-isolated stretching (AIS), the post exercise stretching routine the author uses with the players he works with. With some examples for exercises. 6 benefits of AIS to the player are: 1. AIS helps with the prevention of injuries 2. Increases flexibility and mobility 3. Better care of tendons and ligaments, reducing the risk of muscle strain and tear. 4. Improves oxygenation of the myofacial structures promoting growth and repair. 5. Increases blood circulation and stimulates lymph drainage, which helps eliminate wastes. 6. Speeds up the recovery process enabling the player to intensify their training with less joint and muscular pain.